2012
DOI: 10.1590/s1516-18462012005000040
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos temporais auditivos em adolescentes do 6º ano do ensino fundamental

Abstract: RESUMOObjetivo: esclarecer a relação entre desempenho escolar e aspectos temporais auditivos. Método: estudo descritivo-transversal com amostra de conveniência, composta por 82 estudantes, na faixa etária de 11 a 13 anos, sendo 43 do sexo feminino e 38 do sexo masculino do 6º ano de uma escola de financiamento privado na Região Metropolitana Conflito de interesses: inexistentecapacidades do processamento auditivo, são as habilidades do processamento temporal, uma vez que muitas das características que engloba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
7
0
4
Order By: Relevance
“…One study used a version of Taborga-Lizarro and it found higher percentage of alterations in FPT in a population of children with normal hearing and different levels of school performance, including students with superior academic performance (28) . In another study (29) , a percentage of 49.2% of accuracy for FPT and 67.5% in DPT was observed in the version of Musiek, which is considered altered.…”
Section: Discussionmentioning
confidence: 99%
“…One study used a version of Taborga-Lizarro and it found higher percentage of alterations in FPT in a population of children with normal hearing and different levels of school performance, including students with superior academic performance (28) . In another study (29) , a percentage of 49.2% of accuracy for FPT and 67.5% in DPT was observed in the version of Musiek, which is considered altered.…”
Section: Discussionmentioning
confidence: 99%
“…28 Thus, any inability to sequence the order of occurrence of sound events can impair the perception of verbal and nonverbal sounds, the understanding of information about things, places and events around us, as well as the perception of prosodic aspects of speech and reading. [29][30][31] A study that verified the relationship between academic performance and auditory temporal aspects of adolescents in the 6th grade of elementary school showed that the results of temporal tests were not influenced by the variables: gender, age, musicalization, and manual preference; However, a significant difference was observed between the speechlanguage management variable and the findings obtained in the GIN test. Regarding the academic performance test, it was observed that the subtests that had the greatest influence on the duration pattern (DP) and pitch pattern tests were writing, followed by reading and arithmetic.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the literature used the Pitch Pattern Sequence (PPS) to assess temporal ordering and the sound pattern discrimination in children aged from 7 to 12 years and adults, being scarce the studies that showed its application in children under 7 years old. (6,(19)(20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%